TINDAK TUTUR ILOKUSI PESERTA DISKUSI DALAM ACARA ILC (INDONESIA LAWYERS CLUB) DI STASIUN TELEVISI TV ONE EDISI KASUS DUGAAN KORUPSI SETYA NOVANTO - Ayuri, Septie Miranda; Agustina, Agustina; Juita, Novia (Universitas Negeri Padang, 2018)
This research is about the strategy of telling in the event of ILC (Indonesia Lawyers Club) in TV ONE which is said by the discussion participants on the topic about